Faith-based Social Entrepreneurship: Improving Mosque's Socio-Economic Values in Emerging Country - Ahmad Faiz Khudlari Thoha; Ali Mujahidin (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The religious perspective in the literature on social entrepreneurship remains largely unexplored, resulting in a scarcity of studies that analyze social entrepreneurship through a religious lens. Social entrepreneurship, including its manifestation in religious organizations as faith-based social enterprises, has emerged as a significant innovation in addressing diverse social issues, with the vast number of mosques in Indonesia presenting a promising opportunity to contribute to the betterment of the community's well-being. This study aims to identify the transformation process at the Masjid Ar Rahmah Surabaya and its impacts on social welfare considering its successful establishment as a faith-based social enterprises over the past five years, managing multiple business units and generating social benefits. Employing a case study, data were collected through interviews, observations, and document studies. The findings of the study present a model consisting of stages such as opportunity recognition, business establishment, resource acquisition, and organizational reconfiguration. These insights have implications for addressing social issues and enhancing community welfare in Indonesia and other emerging countries.